Question

Solve the quadratic equation: 2x2+7x+3=0?

Solve the quadratic equation: 2x2+7x+3=0?

Answers

2x2+7x+3=0

(2x+1)(x+3)=0

x= -3, -1/2

#1

x = [ - b ± √ ( b 2 - 4 a c ) ] / 2 a

x = [ - 7 ± √ ( 49 - 24 ) ] / 4

x = [ - 7 ± √ ( 25 ) ] / 4

x = [ - 7 ± 5 ] / 4

x = - 1/2 , x = - 3

OR

( 2 x + 1 ) ( x + 3 ) = 0

x = - 1/2 , x = - 3

#2

Use the quadratic formula to solve the quadratic equation. (-b +- sqrt(b^2 - 4*a*c)) / (2a). BTW, the ^ means raised to a power.

In this case, -7 +- sqrt(7^2 - 4*2*3) / (2*2)

x = -7 +- sqrt(49 - 24) / 4

= (-7 +- sqrt(25)) / 4

= (-7 +- 5) / 4

Therefore, x = (-7 + 5) / 4 = -1/2 = -0.5 OR x = (-7 - 5) / 4 = -12/4 = -3

So, x = -0.5 or -3

Hope this helps.

#3